Pengaruh Kompensasi, Motivasi Kerja, dan Lingkungan Kerja terhadap Turnover Intention Karyawan : Studi Kasus pada PT. XYZ Divisi Kimia Merak - Neta Tertina Aratri; Agrianti Komalasari (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to empirically examine the influence of compensation, work motivation, and work environment on employee turnover intention at PT. XYZ, Kimia Merak Division. This study is expected to contribute both theoretically and practically in the field of human resource management, particularly in reducing employee turnover. The problem of turnover intention is a crucial issue because it can have negative impacts on organizational sustainability, such as increased recruitment costs, disrupted productivity, and the loss of experienced employees. The research method used is a quantitative approach with a purposive sampling technique. The study sample consisted of 75 permanent employees who have worked for at least two years. Data collection was carried out using a questionnaire instrument that has been tested for validity and reliability. Data analysis used multiple linear regression to test the influence of independent variables on the dependent variable. The results of the study indicate that compensation, work motivation, and work environment each have a negative and significant effect on turnover intention. This means that the better the compensation provided, the higher the employee's work motivation, and the more conducive the work environment, the lower the tendency of employees to intend to leave the company. The findings indicate that improving compensation packages, enhancing employee motivation, and maintaining a supportive work environment are crucial strategies to reduce turnover intention. Based on these results, companies are advised to design fair and competitive compensation systems, create programs that enhance intrinsic and extrinsic motivation, and ensure a safe, comfortable, and supportive work environment for employee performance. This way, companies can retain quality human resources and maintain operational stability.